Special MISO-SAR and MIMO-SAR Modes for Bidirectional Imaging - Hai Jiang; Hongjun Song; Lei Guo; Wei Wang (International Journal of Antennas and Propagation)
The paper proposes special multiple-input single-output synthetic aperture radar (MISO-SAR) and multiple-input multiple-output SAR (MIMO-SAR) for bidirectional imaging, which can simultaneously illuminate two areas from different directions in azimuth. For the proposed MISO-SAR, two subpulses with the same carrier frequency and phase coding are transmitted with different azimuth directions by switching the phase coefficients in the transmit modules, and echoes corresponding to the subpulses are received by the main lobe and the first grating lobe of the whole antenna. To suppress mutual interference, the two subpulses are transmitted with different range-frequency bands, and their echoes are demodulated and recorded in different channels in the proposed MIMO-SAR. This paper presents the system design of these modes and analyzes their azimuth ambiguity to signal ratio (AASR). Besides, simulation results on points are carried out to validate the proposed bidirectional imaging modes.